THE EFECTS OF TRANSFER PRICING, THIN CAPITALIZATION, FIRM SIZE, AND TAX HAVEN COUNTRY UTILIZATION ON TAX AGGRESIVENESS - Chamdun Mahmudi; Khayatun Nufus; Safira Gerbiani Said (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research aims to examine the effects of transfer pricing, thin capitalization, firm size, and tax haven country utilization on tax aggresiveness. This study uses manufacturing sector companies listed on Indonesia Stock Exchange (IDX) during 2017 – 2021 period. The total of samples used were 21 manufacturing sector companies for 5 years. This study used multiple linear regression analysis with the assistance of SPSS 25. The results of this research indicated that transfer pricing, thin capitalization, and tax haven country utilization have no effect on tax aggresiveness. While, firm size has positive and significant effect on tax aggresiveness. This researh have an implication for related parties, especially the Directorate General of Taxes of the Republic of Indonesia and taxpayers in minimizing tax aggresiveness